The Tradition of the Original Tenganan People in Preserving Endogamy Marriage in Traditional Village Tenganan Pegringsingan, Bali - Ni Nyoman Putri Nursanti; Wilodati Wilodati; Siti Komariah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to reveal the reason the indigenous Tenganan people preserve endogamous marriage. This descriptive research was conducted in the traditional village of Tenganan Pegringsingan, with data acquisition through document studies, interviews and observations. The results of this study indicate that until now the traditional village community of Tenganan Pegringsingan still preserves and still implements the written rule, namely Awig-Awig . The Tenganan Asli preserve endogamous marriages with the aim of remaining able to become villagers who can control the village government while preserving the traditions of the original Tenganan people. With their uniqueness in using a government system based on the order of marital seniority, the native Tenganan people receive rewards according to their positions in the government system. The condition that is still sustainable until now is reinforced by Shill's theory that the connection of today's society with its past has never died at all. Furthermore, it is said that the link between the present and the past is the basis of tradition.